Cpc2, a Fission Yeast Homologue of Mammalian RACK1 Protein, Interacts with Ran1 (Pat1) Kinase To Regulate Cell Cycle Progression and Meiotic Development - McLeod, Maureen (American Society for Microbiology, 2000)
The Schizosaccharomyces pombe ran1/pat1 gene regulates the transition between mitosis and meiosis. Inactivation of Ran1 (Pat1) kinase is necessary and sufficient for cells to exit the cell cycle and undergo meiosis. The yeast two-hybrid interaction trap was used to identify protein partners for Ran1/Pat1. Here we report the identification of one of these, Cpc2. Cpc2 encodes a homologue of RACK1, a WD protein with homology to the β subunit of heterotrimeric G proteins. RACK1 is a highly conserved protein, although its function remains undefined. In mammalian cells, RACK1 physically associates with some signal transduction proteins, including Src and protein kinase C. Fission yeast cells containing a cpc2 null allele are viable but cell cycle delayed. cpc2Δ cells fail to accumulate in G(1) when starved of nitrogen. This leads to defects in conjugation and meiosis. Copurification studies show that although Cpc2 and Ran1 (Pat1) physically associate, Cpc2 does not alter Ran1 (Pat1) kinase activity in vitro. Using a Ran1 (Pat1) fusion to green fluorescent protein, we show that localization of the kinase is impaired in cpc2Δ cells. Thus, in parallel with the proposed role of RACK1 in mammalian cells, fission yeast cpc2 may function as an anchoring protein for Ran1 (Pat1) kinase. All defects associated with loss of cpc2 are reversed in cells expressing mammalian RACK1, demonstrating that the fission yeast and mammalian gene products are indeed functional homologues.